Finally, a Minimally Invasive Option for Intrahepatic Inferior Vena Cava Invasion by Hepatocellular Carcinoma - Soule, Erik (Gastrointest Tumors, 2018)
BACKGROUND: Major vessel invasion is a late manifestation of hepatocellular carcinoma, which may directly result in mortality if left untreated. Surgical resection may be an option for select patients; however, surgery may be contraindicated. Contraindications include multifocal disease, poor liver reserve, inability to tolerate surgery, and patient preference. Cryoablation is a minimally invasive therapy utilized for treating hepatic neoplasms by subjecting them to extreme cold temperatures. The “thermal sink” effect describes cryoablation near flowing blood such as that found in high volumes within major vascular structures. Thermodynamics dictates that proximity to the flowing intravascular compartment will decrease ice formation, and therefore, tumor destruction. METHODS: This report describes a novel palliative technique to induce temporary cessation of the blood flow in the intrahepatic inferior vena cava (IVC), thus enabling the operator to perform cryoablation targeting invasive cancer within. RESULTS: Adequate ablation using this technique allowed a patient with IVC invasion 9 months of survival. CONCLUSION: Quality of life during this time was maximized, as recovery time from this procedure is minimal.